Collectively Designing CSR Through Meta-Organizations: A Case Study of the Oil and Gas Industry - Berkowitz, Heloïse (Journal of business ethics, 2017)
Few industries have been pressured to develop corporate social responsibility (CSR) standards and policies like oil and gas. This has translated into the creation of non-governmental organizations and branches of the oil and gas firms focused on CSR. However, given the intrinsic complex characteristics of this industry, its global reach, and the fact that its operations affect and involve a wide variety of stakeholders, CSR issues cannot be defined and implemented exclusively at the industry or firm levels, but require the participation of other actors affected directly or indirectly by oil and gas activities. In this paper we argue, first, that oil and gas CSR issues are collectively constructed through meta-organizations (organizations composed by other organizations), and, second, that the complexity and variety of CSR issues require companies to build industry-specific and non-industry-specific collective actions. Based on how oil and gas firms participate in this multi-level co-construction of CSR issues, we created a typology of meta-organizations as infra-sectoral, sectoral, cross-sectoral, and supra-sectoral meta-organizations.